Gross municipal product: the design procedure and application - Dmitry Vasilevich Kolechkov; Jusif Alimovich Gadzhiev; Svyatoslav Anatolievich Timasheff; Maria Nikitichna Makarova (Экономика региона, 2012)
The article is devoted to the actual problem to find the adequate methods to assess the economic performance of municipalities conditioned by their growing independence and role in the development of regional economy. Nowadays many researchers are working on the practical application and testing of various approaches to assessing theterritory economicresults based on thecalculation of gross municipal product (GМP). However, the development of methodological reasonable calculation tools is still at an early stage. In this article presents a simplified method of calculating the gross municipal product, an analysis of the dynamics and territorialindustrial structure GМP, implemented in terms of grouping areas GМP methods hierarchical cluster analysis of the economic characteristics of the obtained clustersbased on systematic occurring in the economic literature, methodological developments in the calculation of gross municipal product, determination of strengths and weaknesses of different methodological approaches